Diagnostic and Prognostic Value of Serum Levels of Progranulin in Egyptian Multiple Myeloma Patients - Manal Elhuseiny Abufarha,; Haytham Mohammad Mostafa,; Ibrahim Ahmed Abdalgwad, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Cancer cells have defects in regulatory mechanisms that usually control cell proliferation and homeostasis. They share crucial alterations in cell physiology, which lead to malignant growth. Tumorigenesis or tumor growth requires a series of events that include constant cell proliferation, promotion of metastasis and invasion, stimulation of angiogenesis, evasion of tumor suppressor factors, and avoidance of cell death pathways. All these events in tumor progression may be regulated by growth factors produced by normal or malignant cells. Aim of the Work: Measuring level of Progranulin (Pgrn) in the serum of adult patients with Multiple myeloma and correlating it with diagnosis and prognosis. Materials and Methods: This study was conducted on 80 subjects (40 patients and 40 age and sex matched healthy subjects) who were attendants to Clinical Hematology unit during the period from July 2021 to Jan 2022. Results: We evaluated the diagnostic value of progranulin in MM patients using the Progranulin level of 20 pg/ml that was sensitive (97.5%) and specific (55%) to differentiate MM patients from healthy controls making it a potential beneficial diagnostic marker for MM. Also We evaluated the prognostic value of progranulin in MM patients using the Progranulin level of 34 pg/ml to define two patient subgroups with low- versus high level correlated respectively with good response versus partial response to treatment after 12 weeks of chemotherapy Conclusion: Serum pgrn level is significantly higher in MM patients than in healthy individuals making pgrn a diagnostic biomarker for MM. Also, Serum pgrn level is significantly higher in MM patients who showed resistance to chemotherapy VCD making progranulin a beneficial prognostic marker in the choice of treatment protocol.